Identification of transient receptor potential channel 4-associated protein as a novel candidate gene causing congenital primary hypothyroidism - Choukair, Daniela; Fredershausen, Birgit; Vick, Philipp; Hermanns, Pia; Weiß, Birgit; Paramasivam, Nagarajan; Schlesner, Matthias; Lornsen, Katharina; Röth, Ralph; Klutmann, Carina; Kreis, Jennifer; Hoffmann, Georg F.; et al. (Hormone research in paediatrics, 2020)
Background:Congenital primary hypothyroidism (CH) is the most common endocrine disorder in neonates. Methods: To identify novel genes, we performed whole exome sequencing (WES) in 6 patients with CH due to thyroid dysgenesis (TD). The potential effects of the most relevant variants were analyzed using in silico prediction tools. The most promising candidate gene, transient receptor potential channel 4-associated protein (TRPC4AP), was sequenced in 179 further patients with TD. Expression ofTRPC4APin human thyroid was investigated using RT-PCR.Trpc4ap- functional analysis was performed inXenopus laevisusing Morpholino (MO) antisense oligomers. Results: WES identified a likely damaging mutation inTRPC4APleading to a de novo stop codon p.Q552*. Targeted sequencing ofTRPC4APdemonstrated gene variants with predicted damaging potential in 5 patients resulting each in an amino acid exchange (p.P706S, p.F729L, p.S777C, and p.N229S). We demonstrated that TRPC4AP is expressed in human thyroid gland tissue. Using Xenopus laevis, we showed that the volume of the tadpole thyroid anlage was reduced by 20% inTrpc4apMO knockdowns compared to controls and by 41% in "Clustered Regularly Interspaced Short Palindromic Repeats"/Cas9-mediated gene knockout experiments. Discussion: A recognized interaction of TRPC4AP and the NF-kappa-B-essential-modulator encoded byIKBKGgene was identified by IPA analysis. IKBKG plays a role in activation of the NF-kappa B-signaling pathway and regulates genes involved in proliferation and survival of thyrocytes and expression of key enzymes of thyroid hormone synthesis. Conclusion: TRPC4AP was identified as a novel candidate gene in TD, but further studies are needed to validate its role in thyroid function.